Nanomaterials for humidity and temperature sensing applications - Ruziana, Mohamed; Ahmad Syakirin, Ismail @ Rosdi; Azianty, Saroni; Mohd Firdaus, Malek
The development of nanomaterials in the field of temperature and humidity sensors has piqued the attention of researchers in recent years, owing to the growing number of applications in the industrial and private sectors as a result of their expanding number of uses. Temperature sensing is the most widely used of all sensing technologies. This phenomenon is used in a variety of applications where knowing and using the actual or relative temperature is absolutely critical. Furthermore, in order to ensure accuracy, other sensors such as pressure, force, flow, level, and position may also require temperature monitoring. Significantly, temperature sensing and a thorough understanding of a material’s thermal behavior are required in order to fully understand how to accurately sense the vast majority of other physical phenomena. Humidity measurement, on the other hand, is used to determine the amount of water vapor present in a gas, which can be either a mixture, such as air, or a pure gas, such as nitrogen or argon. Humidity monitoring has received increasing attention in recent years due to its importance in monitoring and controlling various domestic and industrial environments for gases/air, bulk solids or powders, or in fuels or other liquids, as well as in monitoring and controlling various domestic and industrial environments. As a result, intensive research is being conducted into the development of these sensors with improved sensitivity, good linearity, fast response/recovery, good stability, excellent reproducibility, and impressive selectivity to the target gases at ppm concentrations. This is why nanomaterials with novel fundamental characteristics, such as high specific surface area, ordered mesoporous structure, and high interconnectivity, have emerged as a potential candidate for the development of future sensors. This book chapter summarizes recent developments and considers the impact of nanomaterials on the development of temperature and humidity sensor technology, among other things.